Delayed extradural haemorrhage: a case for intracranial pressure monitoring in sedated children with traumatic brain injury within tertiary centres - Hughes, Anna (BMJ Publishing Group, 2013)
A 15-year-old girl sustained a mild isolated traumatic brain injury  following a pedestrian road traffic accident. She was ventilated for head computed tomography (CT) scan which revealed no intracranial abnormalities. Ventilation was not withdrawn until 15 h later when poor neurological recovery prompted urgent repeat CT, which demonstrated a delayed extradural haemorrhage (EDH). She underwent surgical evacuation, and intracranial pressure (ICP) monitoring was initiated postoperatively. She developed persistently raised ICP resistant to medical therapy, prompting further CT. This showed a recurrence of the delayed EDH requiring further surgical drainage. She made a good neurological recovery. There should be a low threshold for repeat CT to exclude delayed EDH when neurological status is poor despite normal CT soon after initial primary injury. ICP monitoring should be undertaken in children and adolescents who have normal initial CT, but in whom serial neurological assessment is not possible owing to sedation.